Study of the Utilization of Corn Microgreens (Zea mays L.) as a Feed Supplement for Broiler Chickens (Gallus domesticus) - Pradana, Vredy; Haryanta, Dwi; Suryaningsih, Dwie Retna (Journal of Applied Plant Technology, 2025)
Microgreens, the nutrient-packed young seedlings of vegetables and cereals, have emerged as a promising alternative feed source in animal husbandry. This study evaluates the efficacy of corn microgreens as poultry feed compared to conventional dried corn in village chicken production. Using a randomized complete block design, twenty 2-month-old village chickens (average initial weight: 750g) were divided into two groups: one fed with dried corn (control) and another with corn microgreens (treatment). Growth performance was assessed through weekly measurements of body weight, body length, and wing length over a 4-week period. Results indicated significant improvements (p<0.05) in all growth parameters for the microgreen-fed group. The treatment group showed 18% greater weight gain, 12% increased body length, and 15% longer wing development compared to controls. These enhancements are attributed to the higher concentrations of essential nutrients, particularly proteins (23% higher) and antioxidants (40% higher), in corn microgreens versus mature corn. The study demonstrates that corn microgreens can serve as a superior feed alternative, potentially reducing reliance on conventional feeds while improving poultry growth rates. These findings offer valuable insights for small-scale poultry farmers seeking cost-effective, nutrient-dense feeding strategies.